Outcome of the public consultation on the draft Guidance on commodity risk assessment for the evaluation of high risk plants dossiers. Issue 4 (29th April 2019) - ,; Potting, Roel; Dehnen‐Schmutz, Katharina; Miret, Josep Anton Jaques; Jeger, Michael John; Preti, Stefano; Rosace, Maria Chiara; Gardi, Ciro
Abstract : EFSA has carried out a public consultation on the draft Guidance of the EFSA Scientific Panel on Plant Health (PLH Panel) on commodity risk assessment for the evaluation of high risk plants dossiers with the aim of collecting input from the scientific community and all interested parties. Article 42 of the European Regulation (EU) 2016/2031, on the protective measures against pests of plants, introduces the concept of 'high risk plants, plant products and other objects' that are identified on the basis of a preliminary assessment to be followed by a commodity risk assessment. The draft Guidance provided the methodology to be followed when performing a commodity risk assessment for high risk commodities. Following international standards on pest risk analysis this Guidance describes a two‐step approach for the assessment of pest risk associated with a specified commodity. In the first step, pests associated with the commodity that may require risk mitigation measures are identified. In the second step, the overall efficacy of proposed risk reduction options for each pest is evaluated. A conclusion on the pest freedom status of the commodity is achieved. The method allows key uncertainties to be identified. Following the endorsement of the draft Guidance by the PLH Panel, the public consultation was launched on 14 December 2018 and closed on 24 January 2019. EFSA received 56 comments on the draft Guidance from four interested parties. This technical report on the outcome of the public consultation on the draft Guidance summarises the comments received during the public consultation and presents the responses of the PLH Panel. The PLH Panel prepared an updated version of the draft Guidance taking into account the comments received. The Guidance was adopted at the PLH Panel plenary meeting on 28 March 2019, (EFSA PLH panel, 2019) and is published in the EFSA Journal.